Temperature‐Dependent Terahertz Emission from Co/Mn2Au Spintronic Bilayers. Issue 10 (2nd August 2021) - Ni, Yangyang; Jin, Zuanming; Song, Bangju; Zhou, Xiaofeng; Chen, Haiyang; Song, Cheng; Peng, Yan; Zhang, Chao; Pan, Feng; Ma, Guohong; Zhu, Yiming; Zhuang, Songlin
Abstract : Recently, ferromagnetic/nonmagnetic heavy metal heterostructures have been intensively investigated as terahertz (THz) emitters. The interconversion of spin‐to‐charge dynamics plays a central role for efficient emission of THz electromagnetic pulses. However, a direct observation of spin–charge interconversion in antiferromagnetic (AFM) materials occurring on the sub‐picosecond time scale remains a challenge. Herein, the magnetic‐field‐, pump‐fluence‐, and polarization‐dependent THz emission behaviors by a femtosecond optical pump in cobalt (Co)/Mn2 Au nanometer heterostructure are experimentally investigated. The Co/Mn2 Au bilayer generates sizable THz signals, whereas the Mn2 Au/Pt bilayer does not show any THz emission. In addition, the thickness‐ and temperature‐dependent THz emission measurements indicate a direct relation between the THz amplitude and the conductivity of AFM Mn2 Au layer. The results obtained will not only promote the fundamental understanding of ultrafast spin–charge interconversion in Co/Mn2 Au heterostructures, but also provide a possibility of spectroscopic‐based spin current detector at THz‐frequency range. Abstract : Terahertz radiation is generated from the Co/Mn2 Au heterostructure using femtosecond laser pulses. The inverse spin Hall effect in the Mn2 Au antiferromagnetic layer is indispensable to explain the dependence of THz emission on the pump and magnetic‐field directions. The characteristics of THz emission provide the understanding of spin‐to‐charge interconversion on a picosecond time scale, and a possibility of spin current detector at THz‐frequency range.